Amar Ma'ruf Nahi Munkar Sebagai Model Pendidikan Kritis Profetik - Diah Irdiyana Rizqi; Muhammad Akmansyah; A’vi Amelia; A’la Nirotul Fikri; Amia Kasmila (Kartika: Jurnal Studi Keislaman, 2026)
Islamic education requires a paradigm that is not only oriented toward knowledge transfer, but also shapes students' critical awareness, moral character, and social responsibility. This article analyzes the concept of amar ma'ruf nahi munkar (enjoining good and forbidding evil) as a model of prophetic critical education through a qualitative approach and library research on Qur'anic verses, hadith, and relevant literature. The findings show that amar ma'ruf functions as participatory and transformative education representing humanization, nahi munkar serves as social control in academic settings reflecting liberation, while the ethics of criticism and moral advocacy demonstrate the dimension of transcendence grounded in faith in Allah SWT. These three dimensions are integrated to shape students who are critical, moral, and responsible both socially and spiritually. Thus, amar ma'ruf nahi munkar can be understood as an educational model that not only teaches moral values but also encourages active participation and social transformation. This model is relevant for addressing contemporary challenges, such as moral degradation and social inequality, by offering a holistic approach that combines intellectual, spiritual, and social aspects. Prophetic critical education based on amar ma'ruf nahi munkar is expected to produce a generation that is not only cognitively intelligent but also possesses strong social sensitivity and moral commitment in community life.